A diaphragm, its preparation method and use

CN122907852APending Publication Date: 2026-10-13JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611079825.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]然而,上述现有技术在推广应用过程中仍面临一些实际困难

Benefits of technology

[0008]本申请通过在基膜上设置含二氧化硅的第一涂层和含陶瓷材料第二涂层,并在两者的交界区域处形成同时含有二氧化硅和陶瓷材料的界面过渡层,且限定二氧化硅的颗粒粒径小于陶瓷材料的颗粒粒径;界面过渡层在第一涂层和第二涂层之间形成了连续的结构过渡,避免了因界面应力集中导致的层间剥离问题。同时,界面过渡层中部分小粒径的二氧化硅颗粒能够嵌入大粒径陶瓷材料颗粒之间的孔隙中,形成颗粒嵌套结构,显著增强了第一涂层与第二涂层之间的结合力,使隔膜具有较高的剥离强度,从而有效防止第二涂层中陶瓷材料的脱落,降低卷绕式锂电池R角失效风险;更重要的是,在高温下当基膜受热收缩时,界面过渡层内紧密相依的大小颗粒之间产生相互作用力,抵抗颗粒的相对滑移,第一涂层和第二涂层仍能够保持结构完整性,从而保持隔膜主体的结构完整性,降低正负极短接风险、电池发生热失控的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application specifically discloses a diaphragm, a preparation method and application thereof. The diaphragm comprises a base film, a first coating layer arranged on at least one surface along the thickness direction of the base film, the first coating layer comprising silicon dioxide, a second coating layer arranged on the surface of the first coating layer away from the base film, the second coating layer comprising a ceramic material, and an interface transition layer between the first coating layer and the second coating layer, the interface transition layer containing both the silicon dioxide and the ceramic material, wherein the particle size of the silicon dioxide is smaller than that of the ceramic material. The diaphragm has high peeling strength and excellent thermal stability, and can effectively reduce the risk of thermal runaway of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery technology, and in particular to a separator, its preparation method, and its application. Background Technology

[0002] Lithium-ion battery separators are primarily made of polyolefin materials, which possess excellent chemical stability and mechanical strength, leading to their widespread use in the lithium-ion battery field. However, as market demands for higher energy density and safety performance in lithium-ion batteries continue to increase, the insufficient thermal stability of polyolefin separators has become increasingly prominent. When operating under conditions of internal short circuits, overcharging, or high temperatures, the separator is prone to thermal shrinkage, leading to direct contact between the positive and negative electrodes, potentially causing battery combustion or even explosion. This has become a key bottleneck restricting the improvement of lithium-ion battery safety performance.

[0003] To address the aforementioned issues, those skilled in the art have attempted to coat the surface of polyolefin-based membranes with ceramic materials, utilizing the high thermal stability of ceramic materials to suppress the thermal shrinkage of the membrane. Various ceramic-coated membrane solutions have been disclosed in the prior art. For example, coating a polyolefin-based membrane with a silica aerogel composite layer to improve the membrane's liquid absorption and anti-spiking ability; coating the base membrane with a high-temperature resistant polyimide polymer to improve the membrane's thermal stability and wettability; or coating the membrane with modified polyvinylidene fluoride to enhance its wettability and absorption rate of the electrolyte. These solutions all improve the thermal stability of the membrane by introducing high-temperature resistant materials, thus improving the membrane's safety performance to some extent.

[0004] However, the aforementioned existing technologies still face some practical difficulties in their widespread application. On the one hand, the synthesis processes of some high-performance high-temperature resistant materials, such as polyimide and modified polyvinylidene fluoride, are complex, resulting in high manufacturing costs and limiting their application in large-scale production. On the other hand, the preparation of multilayer ceramic coatings often involves multiple coating processes, resulting in a long process flow and reduced production efficiency. Furthermore, how to form a more stable bond between different coatings and between the coating and the base film, so that the diaphragm maintains its overall structural integrity under high-temperature conditions, remains a technical problem of ongoing concern in this field.

[0005] Therefore, developing a membrane with strong interfacial bonding and excellent thermal stability remains a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] To address the technical problems in the prior art, this application provides a diaphragm, its preparation method, and its application.

[0007] In a first aspect, this application provides a diaphragm, which adopts the following technical solution: A diaphragm includes a base film; a first coating disposed on at least one surface along the thickness direction of the base film, the first coating comprising silicon dioxide; a second coating disposed on the surface of the first coating away from the base film, the second coating comprising a ceramic material; and an interface transition layer located between the first coating and the second coating, the interface transition layer containing both the silicon dioxide and the ceramic material; wherein the particle size of the silicon dioxide is smaller than the particle size of the ceramic material.

[0008] This application involves forming a first coating containing silica and a second coating containing ceramic material on a base film, and creating an interface transition layer containing both silica and ceramic material at the interface between the two, with the silica particle size being smaller than that of the ceramic material. This interface transition layer creates a continuous structural transition between the first and second coatings, avoiding interlayer delamination caused by interface stress concentration. Simultaneously, some small-diameter silica particles in the interface transition layer can embed into the pores between large-diameter ceramic material particles, forming a nested particle structure. This significantly enhances the bonding force between the first and second coatings, giving the separator high peel strength and effectively preventing the ceramic material in the second coating from detaching, thus reducing the risk of R-corner failure in wound lithium batteries. More importantly, when the base film shrinks due to heat at high temperatures, the closely interdependent particles of varying sizes within the interface transition layer generate interaction forces, resisting relative particle slippage. The first and second coatings maintain structural integrity, thereby preserving the structural integrity of the separator body and reducing the risk of short circuits between the positive and negative electrodes and the risk of thermal runaway in the battery.

[0009] Preferably, the silicon dioxide has a particle size of 50-200 nm, and / or the ceramic material has a particle size of 200-500 nm.

[0010] Preferably, the porosity of the interface transition layer is less than that of the second coating.

[0011] Preferably, the porosity of the interface transition layer is 10%-20%, and / or the porosity of the second coating is 20%-40%.

[0012] Preferably, the first coating further includes silanol groups.

[0013] Preferably, the ceramic material includes at least one of alumina, zirconium dioxide, and titanium dioxide.

[0014] Preferably, the thickness of the first coating is 0.5-1.5 μm, and / or the thickness of the second coating is 2-3 μm, and / or the thickness of the interface transition layer is 0.5-1.6 μm.

[0015] Secondly, this application provides a method for preparing a diaphragm, employing the following technical solution: A method for preparing a diaphragm includes the following steps: S1, mixing an alkoxysilane compound with an alcohol solvent to obtain a first slurry; mixing an adhesive with water to obtain a glue solution; mixing the glue solution with a ceramic material to obtain a second slurry; S2, simultaneously coating the first slurry and the second slurry onto a base film to form a wet first slurry layer and a second slurry layer; wherein the first slurry layer is located between the base film and the second slurry layer; S3: drying and curing the coated base film obtained in S2 to obtain a diaphragm containing a first coating layer, an interface transition layer, and a second coating layer.

[0016] Preferably, S1 satisfies at least one of the following characteristics: (a) the alkoxysilane compound includes at least one of methyl orthosilicate, ethyl orthosilicate, methyl ethyl orthosilicate, propyl orthosilicate, and methyl propyl orthosilicate; (b) the mass ratio of the ceramic material to the binder is (60-120):1; (c) the first slurry has a solid content of 20%-60% and a viscosity of 5-50 mPa·s; (d) the second slurry has a solid content of 30%-40% and a viscosity of 60-140 mPa·s.

[0017] Thirdly, this application provides a lithium battery, which adopts the following technical solution: A lithium battery includes a positive electrode, a negative electrode, and a separator as described above or a separator prepared by the method described above. Detailed Implementation

[0018] To better understand and implement this application, the technical solutions of this application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only some of the embodiments of this application, and not all of them.

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application.

[0020] Unless otherwise stated, all numerical values ​​for the amounts of expressed components, reaction conditions, etc., used in the specification and claims are to be understood as being modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values ​​that can be varied to obtain the desired performance.

[0021] Unless otherwise stated, the terms “a,” “an,” “an,” and “the” as used in this specification are intended to include “at least one” or “one or more.” For example, “a component” refers to one or more components, and therefore more than one component may be considered and may be employed or used in the implementation of the described embodiments.

[0022] The word “and / or” as used in this article refers to one or all of the elements mentioned.

[0023] The terms "include" and "contain" as used in this article cover both cases where only the mentioned elements exist and cases where other unmentioned elements exist in addition to the mentioned elements.

[0024] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0025] A first aspect of this application provides a diaphragm comprising a base film; a first coating disposed on at least one surface along the thickness direction of the base film, the first coating comprising silicon dioxide; a second coating disposed on the surface of the first coating away from the base film, the second coating comprising a ceramic material; and an interface transition layer located between the first coating and the second coating, the interface transition layer containing both the silicon dioxide and the ceramic material; wherein the particle size of the silicon dioxide is smaller than the particle size of the ceramic material.

[0026] This application involves forming a first coating containing silica and a second coating containing ceramic material on a base film, and creating an interface transition layer containing both silica and ceramic material at the interface between the two, with the silica particle size being smaller than that of the ceramic material. This interface transition layer creates a continuous structural transition between the first and second coatings, avoiding interlayer delamination caused by interface stress concentration. Simultaneously, some small-diameter silica particles in the interface transition layer can embed into the pores between large-diameter ceramic material particles, forming a nested particle structure. This significantly enhances the bonding force between the first and second coatings, giving the separator high peel strength and effectively preventing the ceramic material in the second coating from detaching, thus reducing the risk of R-corner failure in wound lithium batteries. More importantly, when the base film shrinks due to heat at high temperatures, the closely interdependent particles of varying sizes within the interface transition layer generate interaction forces, resisting relative particle slippage. The first and second coatings maintain structural integrity, thereby preserving the structural integrity of the separator body and reducing the risk of short circuits between the positive and negative electrodes and the risk of thermal runaway in the battery.

[0027] In one embodiment of this application, the particle size of the silicon dioxide is 50-200 nm, and / or the particle size of the ceramic material is 200-500 nm.

[0028] This application further optimizes the particle size of silica and the ceramic material, achieving an optimal match between particle size and particle size. When the silica particle size is within the range of 50-200 nm, it can effectively embed itself into the pores of ceramic material particles of 200-500 nm to form a relatively dense interfacial transition layer, without excessively blocking ion transport channels. This avoids the problems of lithium-ion transport being hindered and battery internal resistance increasing due to excessively small particle size, and also avoids the problems of ineffective embedding and reduced densification effect of the interfacial transition layer due to excessively large particle size. Controlling the particle size within the above range achieves an optimal balance between thermal stability, interfacial adhesion, ion conductivity, and cycle life.

[0029] In one embodiment of this application, the porosity of the interface transition layer is less than that of the second coating.

[0030] This application achieves a two-stage structure in the separator by limiting the porosity of the interface transition layer to be less than that of the second coating. This structure combines a dense interface transition layer with a porous second coating in the thickness direction. First, the dense structure of the interface transition layer originates from the effective filling of the pores of the ceramic material particles by small-diameter silica particles. This anchors the large-diameter ceramic particles in the second coating near the interface, effectively resisting the relative slippage and rearrangement of particles when the base film shrinks due to heat. Simultaneously, the porous structure of the second coating can buffer thermal stress to a certain extent, preventing the coating from becoming brittle due to excessive density. The synergistic effect of these two elements allows the entire composite coating to maintain structural integrity at high temperatures, effectively blocking contact between the positive and negative electrodes, thereby significantly reducing the risk of battery thermal runaway. Secondly, the two-stage structure optimizes the electrolyte's absorption and retention performance. During electrolyte injection, the loose structure of the second coating has a higher porosity, enabling rapid absorption of the electrolyte and reducing permeation resistance. Meanwhile, the dense structure of the interfacial transition layer has a lower porosity, creating capillary forces that firmly lock the electrolyte inside the separator. This combination of a loose front and a tight back structure allows the electrolyte to enter the separator quickly while minimizing loss during cycling, thus balancing injection efficiency and retention capacity. Furthermore, the two-stage structure addresses both interfacial bonding and ion transport requirements. The dense structure of the interfacial transition layer ensures high bonding strength between the first and second coatings, preventing coating detachment or powdering. The loose structure of the main body of the second coating provides unobstructed transport channels for lithium ions, ensuring the battery's rate performance. This allows the separator to achieve excellent interfacial bonding and thermal stability without sacrificing electrochemical performance.

[0031] In one embodiment of this application, the porosity of the interface transition layer is 10%-20%, and / or the porosity of the second coating is 20%-40%.

[0032] In one embodiment of this application, the first coating further includes silanol groups.

[0033] During the lithium-ion battery electrolyte filling process, the electrolyte first contacts the separator surface and then permeates along the separator pores into the pores of the active material on both sides of the electrode. Because the surface of the first coating contains silanol groups, these polar functional groups have good compatibility with the polar components in the electrolyte, significantly reducing the interfacial tension between the electrolyte and the first coating, thereby reducing the resistance to electrolyte penetration into the separator pores. This improved interfacial compatibility allows the electrolyte to spread and permeate more quickly and evenly within the separator. Simultaneously, the presence of silanol groups significantly improves the efficiency of the filling process: on the one hand, the filling time is significantly shortened, increasing production efficiency; on the other hand, the electrolyte spreads more evenly on the separator surface, reducing electrolyte overflow caused by poor permeation and lowering the risk of electrolyte waste and contamination.

[0034] In one embodiment of this application, the ceramic material includes at least one of alumina, zirconium dioxide, and titanium dioxide.

[0035] In one embodiment of this application, the ceramic material has a Vickers hardness of 800-1500 HV and a melting point of 1830-2680℃.

[0036] The ceramic material in the second coating of this application has high thermal stability and good mechanical strength. It can maintain structural stability within the operating temperature range of lithium batteries, providing reliable rigid skeleton support for the separator and also helping to improve the thermal stability of the separator.

[0037] In one embodiment of this application, the thickness of the first coating is 0.5-1.5 μm, and / or the thickness of the second coating is 2-3 μm, and / or the thickness of the interface transition layer is 0.5-1.6 μm.

[0038] This application achieves optimal matching of the functions of each coating by optimizing the thickness of the first coating, the second coating, and the interface transition layer. The first coating provides small-diameter silica particles to form the interface transition layer and utilizes the silanol groups therein to improve electrolyte wettability. When the thickness of the first coating is too small, it is difficult to form a complete first coating on the base film surface, resulting in discontinuity of the interface transition layer and decreased thermal stability. When the thickness of the first coating is too large, the excessively thick first coating increases the lithium-ion transport path, leading to an increase in battery internal resistance. The second coating provides rigid skeleton support to prevent deformation such as bulging and curling of the separator at room temperature. By optimizing the thickness of the second coating, sufficient mechanical strength can be provided without excessively increasing the total thickness of the separator, which would affect the battery energy density. If the thickness of the second coating is too small, its coverage is insufficient, making it difficult to effectively suppress the thermal shrinkage of the base film and increasing the risk of thermal shrinkage. If the thickness is too large, the overall thickness of the separator increases, resulting in a higher battery assembly rate and an increased defect rate in the finished product thickness. The thickness of the interface transition layer reflects the depth to which small silica particles are embedded in large ceramic particles. When the thickness of the interface transition layer is moderate, it indicates that the small silica particles have been fully embedded in the pores of the large ceramic particles, while the first coating still retains sufficient thickness to perform its function of improving wettability. If the thickness of the interface transition layer is too small, it indicates that the small silica particles are not embedded enough and the interlayer bonding force is weak. If the thickness of the interface transition layer is too large, it may mean that the first coating has penetrated excessively into the second coating, resulting in a reduction in the thickness of the first coating itself, making it difficult to form a complete cover layer on the surface of the base film.

[0039] A second aspect of this application provides a method for preparing a diaphragm, comprising the following steps: S1: Mix an alkoxysilane compound with an alcohol solvent to obtain a first slurry; mix an adhesive with water to obtain a glue solution; mix the glue solution with a ceramic material to obtain a second slurry; S2: Coat the first slurry and the second slurry simultaneously onto a base film to form a wet first slurry layer and a second slurry layer; wherein the first slurry layer is located between the base film and the second slurry layer; S3: Dry and cure the coated base film obtained in S2 to obtain a diaphragm containing a first coating layer, an interface transition layer, and a second coating layer.

[0040] The preparation method of this application, through a unique process design, simultaneously coats an alcoholic solution of organosilicon material and an aqueous slurry of ceramic material onto a base film. The high-temperature, high-humidity environment created by the moisture in the second slurry and the drying and curing process causes the organosilicon material to undergo in-situ hydrolysis before the first slurry has cured, resulting in the following technical effects: Firstly, the alcohol solvent in the first slurry can effectively wet the hydrophobic polyolefin base film, laying the foundation for uniform coating coverage. At the same time, the alcohol solvent and the binder aqueous solution in the second slurry are completely miscible, resulting in bidirectional mass exchange at the interface between the two layers: on the one hand, water permeates from the second slurry to the first slurry layer, providing the necessary water source for the subsequent in-situ hydrolysis of the organosilicon material; on the other hand, binder molecules migrate to the first slurry layer under the action of concentration gradient and gravity, and further permeate towards the base film. The permeated binder molecules solidify as the solvent evaporates during the subsequent drying process, and are evenly distributed between the silica particles in the final first coating and on the surface of the base film, forming a continuous bonding network spanning the first and second coatings, firmly connecting the silica particles, ceramic material particles and the base film together, providing a basic guarantee for the structural stability of the entire composite coating. Secondly, thanks to the moisture obtained by the first slurry from the second slurry, the organosilicon material undergoes in-situ hydrolysis in the wet stage, generating silica particles with smaller particle size and more uniform distribution. Compared with directly adding pre-formed silica particles, the small particles generated in-situ have higher activity and can naturally migrate into the pores of the large ceramic particles, forming in-situ filling rather than simple physical mixing. This process directly forms an interface transition layer containing both small silica particles and large ceramic particles, making the porosity of the interface transition layer smaller than that of the second coating. This transition layer is the structural basis for achieving high peel strength and thermal stability in the future. Third, by controlling the degree of hydrolysis, an appropriate amount of silanol groups are retained in the first coating. These silanol groups can significantly improve the compatibility between the membrane and the electrolyte, reduce the resistance of electrolyte penetration into the membrane pores, and macroscopically manifest as improved injection efficiency, shorter injection time, and reduced electrolyte overflow. On the other hand, the silanol groups generated by hydrolysis can chemically bond (covalent or hydrogen bonds) with the functional groups on the surface of the second coating. This chemical bonding, together with the aforementioned nested particle structure, significantly improves the bonding strength between the first and second coatings, effectively preventing the second coating from peeling off or pulverizing during use. Fourth, the one-time coating process allows the two slurry layers to permeate each other in a wet state, forming a continuous transition structure. This avoids the interface contamination and structural defects that may result from step-by-step coating, simplifying the production process.

[0041] In one embodiment of this application, S1 satisfies at least one of the following features: (a) the alkoxysilane compound includes at least one of methyl orthosilicate, ethyl orthosilicate, methyl ethyl orthosilicate, propyl orthosilicate, and methyl propyl orthosilicate; (b) the mass ratio of the ceramic material to the binder is (60-120):1; (c) the first slurry has a solid content of 20%-60% and a viscosity of 5-50 mPa·s; (d) the second slurry has a solid content of 30%-40% and a viscosity of 60-140 mPa·s.

[0042] This application optimizes and limits the slurry formulation and process parameters of the preparation method. The setting of these parameters provides a fundamental guarantee for the realization of the aforementioned process effects, specifically in the following aspects: Firstly, organosilicon materials such as methyl orthosilicate, ethyl orthosilicate, methyl ethyl orthosilicate, propyl orthosilicate, and methyl propyl orthosilicate can all undergo hydrolysis under high temperature and high humidity conditions to generate silica particles, and the hydrolysis products all contain silanol groups. This wide range of material selection makes the preparation method of this application have good raw material adaptability. Different organosilicon materials can be flexibly selected according to factors such as cost and supply without affecting the formation of the interface transition layer and the nested particle structure. Secondly, the preferred solid content of the first slurry provides material assurance for the integrity of the first coating and particle filling. If the solid content is too low, the supply of organosilicon material will be insufficient, making it difficult to form a continuous and complete first coating on the base film surface after hydrolysis, and the interface transition layer cannot be fully formed due to the lack of small particle sources. If the solid content is too high, the slurry viscosity will be too high, which is not conducive to the uniform spreading and wetting of the alcohol solvent on the base film surface. Third, the optimal mass ratio of ceramic material to binder balances pore structure and mechanical strength. When the binder content is relatively low, sufficient pore space is retained between ceramic particles, creating conditions for the subsequent embedding of small silica particles. If the binder ratio is too high, it will block the pores between ceramic particles, hindering the filling of small particles and making it difficult to form an interface transition layer. At the same time, this ratio ensures the presence of sufficient binder: on the one hand, some binder can maintain the structural integrity of the second coating after migrating to the first slurry layer; on the other hand, the binder that penetrates into the first coating is sufficient to form a continuous bonding network spanning the two layers, firmly anchoring the particles and the base film. Fourth, if the solid content of the second slurry is too low, there will be too much water in the slurry, which may result in an excessively thin coating and excessive drying shrinkage; if the solid content is too high, there will be insufficient water, which will make it difficult to provide sufficient water for the hydrolysis of the organosilicon material in the first slurry, thus affecting the formation of the interfacial transition layer. By further controlling the viscosity of the second slurry, the uniformity and stability of the coating during the coating process are ensured, avoiding sagging or uneven coating, and the slurry has suitable fluidity, which is conducive to solvent miscibility and binder migration.

[0043] In one embodiment of this application, the temperature during the drying and curing process in S3 is 45-70°C.

[0044] In one embodiment of this application, the drying and curing process in S3 is carried out by segmented temperature control in a multi-section oven.

[0045] In one embodiment of this application, the drying and curing process uses a five-section oven, with the first to fifth oven zones arranged sequentially along the coating direction, wherein: the temperature of the first oven zone is 45-60℃, the temperature of the second oven zone is 50-65℃, the temperature of the third oven zone is 55-70℃, the temperature of the fourth oven zone is 50-65℃, and the temperature of the fifth oven zone is 45-60℃.

[0046] A third aspect of this application provides a lithium battery, including a positive electrode, a negative electrode, a separator as described above, or a separator prepared by the method described above.

[0047] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0048] Example 1 1. Preparation of the diaphragm The preparation method of the diaphragm includes the following steps: S1, alkoxysilane compound (tetraethyl orthosilicate) and alcohol solvent (ethanol) are mixed at a mass ratio of 1:1 to obtain a first slurry with a solid content of 50% and a viscosity of 18 mPa·s; A binder (carboxymethyl cellulose) is mixed with water to obtain a slurry with a solid content of 4% and a viscosity of 1000 mPa·s. The slurry is then mixed with a ceramic material (alumina) in a mass ratio of 90:1 to the binder. Water is added to adjust the viscosity to obtain a second slurry with a solid content of 36% and a viscosity of 70 mPa·s. S2, using a slot extrusion coating combined with a dual-feed system, the first slurry and the second slurry are simultaneously coated on the base film (the flow rate of the first slurry is 14.5 L / min, and the flow rate of the second slurry is 20.4 L / min), forming a wet first slurry layer and a wet second slurry layer; wherein, the first slurry layer is located between the base film and the second slurry layer; S3: The coated base film obtained in S2 is placed in a 5-section oven (temperatures are 55℃, 60℃, 66℃, 62℃, and 58℃ respectively, and the air frequency is 47 Hz, 47 Hz, 48 Hz, 48 Hz, and 47 Hz respectively; the conveyor speed is 20m / min) for drying and curing treatment; a first coating with a thickness of 1.05μm (silica particle size 121nm), an interface transition layer with a thickness of 0.85μm and a porosity of 15% and a second coating with a thickness of 2.03μm and a porosity of 35% (alumina particle size 281nm) are formed on the surface of the base film, thus obtaining the diaphragm.

[0049] 2. Preparation of the positive electrode sheet Lithium iron phosphate, carbon nanotubes, conductive carbon black, and PVDF were mixed in a mass ratio of 96.3:1.5:0.7:1.5 and NMP was added to form a slurry. The slurry was then coated, rolled, and slit to form a positive electrode sheet.

[0050] 3. Preparation of negative electrode sheet Graphite, CMC, conductive carbon black, and SBR are mixed in a mass ratio of 96.5:1.2:0.5:1.8, water is added to form a slurry, which is then coated, rolled, and slit to form a negative electrode sheet.

[0051] 4. Battery manufacturing The positive electrode, negative electrode, and the aforementioned separator are wound together and then assembled, formed, and capacity tested to produce a square aluminum-cased lithium iron phosphate battery.

[0052] Example 2 The difference between this embodiment and Embodiment 1 lies in the preparation of the diaphragm, specifically including the following steps: S1, alkoxysilane compound (methyl orthosilicate) and alcohol solvent (ethanol) are mixed at a mass ratio of 1:1 to obtain a first slurry with a solid content of 30% and a viscosity of 9 mPa·s; A binder (carboxymethyl cellulose) is mixed with water to obtain a slurry with a solid content of 4% and a viscosity of 1000 mPa·s. The slurry is then mixed with a ceramic material (zirconia) at a mass ratio of 120:1. Water is added to adjust the viscosity to obtain a second slurry with a solid content of 30% and a viscosity of 60 mPa·s. S2, using a slot extrusion coating combined with a dual-feed system, the first slurry and the second slurry are simultaneously coated on the base film (the flow rate of the first slurry is 14.8 L / min, and the flow rate of the second slurry is 21.5 L / min), forming a wet first slurry layer and a wet second slurry layer; wherein, the first slurry layer is located between the base film and the second slurry layer. S3: The coated base film obtained in S2 is placed in a 5-section oven (temperatures are 47℃, 50℃, 56℃, 52℃, and 48℃ respectively, and the air frequency is 42Hz, 42Hz, 43Hz, 43Hz, and 42Hz respectively; the conveyor speed is 20m / min) for drying and curing treatment; a first coating with a thickness of 1.12μm (silica particle size 118nm), an interface transition layer with a thickness of 1.38μm, and a second coating with a thickness of 2.35μm (zirconia particle size 284nm) are formed on the surface of the base film to obtain the diaphragm.

[0053] All other steps and parameter settings are consistent with those in Example 1.

[0054] Example 3 The difference between this embodiment and Embodiment 1 is that the oven temperatures are 45℃, 45℃, 51℃, 47℃, and 45℃ respectively, and the air frequencies are 39Hz, 39Hz, 40Hz, 39Hz, and 38Hz respectively. The conveyor belt speed is 14m / min. The thickness of the first coating is 1.06μm (silica particle size 94nm); the thickness of the second coating is 2.12μm (alumina particle size 283nm); the porosity of the second coating is 35%; the porosity of the interface transition layer is 12%; and other steps and parameter settings are consistent with Embodiment 1.

[0055] Example 4 The difference between this embodiment and Embodiment 1 is that the oven temperatures are 50℃, 56℃, 64℃, 60℃, and 52℃ respectively, and the air frequencies are 49Hz, 49Hz, 40Hz, 49Hz, and 48Hz respectively. The conveyor belt speed is 25m / min. The thickness of the first coating is 1.23μm (silica particle size 135nm); the thickness of the second coating is 2.01μm (alumina particle size 278nm); the porosity of the second coating is 38%; the porosity of the interface transition layer is 18%; and other steps and parameter settings are consistent with Embodiment 1.

[0056] Example 5 The difference between this embodiment and Embodiment 1 is that the temperature of all five oven sections in S3 during the drying and curing process is 40°C; all other steps and parameter settings are consistent with Embodiment 1.

[0057] Example 6 The difference between this embodiment and embodiment 1 is that the temperature of all five ovens in S3 during the drying and curing process is 75°C; all other steps and parameter settings are consistent with those in embodiment 1.

[0058] Example 7 The difference between this embodiment and Embodiment 1 is that the flow rate of the first slurry is adjusted to 9.2 L / min, the thickness of the first coating is 0.51 μm, the flow rate of the second slurry is adjusted to 31.2 L / min, and the thickness of the second coating is 2.77 μm; other steps and parameter settings are consistent with Embodiment 1.

[0059] Example 8 The difference between this embodiment and Embodiment 1 is that the flow rate of the first slurry is adjusted to 18.1 L / min, the thickness of the first coating is 1.38 μm, the flow rate of the second slurry is adjusted to 16.9 L / min, and the thickness of the second coating is 2.05 μm; all other steps and parameter settings are consistent with Embodiment 1.

[0060] Comparative Example 1 The difference between this comparative example and Example 1 is that the diaphragm was prepared using a method comprising the following steps: S1: Carboxymethyl cellulose (CMC) is mixed with water to prepare a glue solution, resulting in a glue solution with a solid content of 4% and a viscosity of 1000 mPa·s. Silica (SiO2) is added to the glue solution, with a mass ratio of silica to CMC of 90:1. Water is added to adjust the viscosity, resulting in a first slurry with a solid content of 36% and a viscosity of 60 mPa·s. Carboxymethyl cellulose (CMC) was mixed with water to prepare a slurry with a solid content of 4% and a viscosity of 1000 mPa·s. A ceramic material (alumina Al2O3) was added to the slurry at a mass ratio of 90:1 to CMC. Water was added to adjust the viscosity to obtain a second slurry with a solid content of 36% and a viscosity of 70 mPa·s. S2: Coat the surface of a 9μm thick PE base film with the first slurry, place it in an oven for drying and baking, and adjust the temperature of the five oven sections to 45℃, 45℃, 45℃, 45℃, 45℃, 45℃ in sequence; the air frequency to 45Hz, 48Hz, 48Hz, 48Hz, 45Hz, and the belt speed to 20m / min to obtain the pretreated base film. S3: Apply the second slurry to the surface of the pretreated base film coated with the first slurry, place it in an oven for drying and baking, and adjust the temperature of the five oven sections to 45℃, 45℃, 45℃, 45℃, 45℃ in sequence; the air frequency to 45Hz, 48Hz, 48Hz, 48Hz, 45Hz in sequence; and the belt speed to 20m / min to obtain the diaphragm.

[0061] Comparative Example 2 The difference between this comparative example and Example 1 is that the positions of the first and second coatings in the diaphragm are reversed; all other steps and parameter settings are the same as in Example 1.

[0062] Comparative Example 3 The difference between this comparative example and Example 1 is that water was used as the solvent in the preparation of the first slurry, and ethanol was used as the solvent in the preparation of the second slurry; all other steps and parameter settings are the same as in Example 1.

[0063] Comparative Example 4 The difference between this comparative example and Example 1 is that the diaphragm was prepared using a method comprising the following steps: S1: Carboxymethyl cellulose (CMC) is mixed with water to prepare a gel solution with a solid content of 4% and a viscosity of 1000 mPa·s. Silica (SiO2) and ceramic material (Al2O3) in a mass ratio of 1:1 are added to the gel solution. The total mass ratio of silica and ceramic material to CMC is 90:1. Water is added to adjust the viscosity to obtain a mixture with a solid content of 36% and a viscosity of 60 mPa·s. S2: A mixed slurry is coated on the surface of a 9μm thick PE base film, and then placed in an oven for drying and baking. The temperatures of the five oven sections are adjusted sequentially to 55℃, 60℃, 66℃, 62℃, and 58℃, and the air frequencies are sequentially 47 Hz, 47 Hz, 48 Hz, 48 Hz, and 47 Hz. The conveyor belt speed is 20m / min, and a diaphragm is obtained. Test methods I. Heat Shrinkage Rate Test (1) Mark the longitudinal and transverse measurement lines 10 mm from the edge of the diaphragm sample, and measure the original lengths with calipers: L0 (MD) and W0 (TD), accurate to 0.01 mm; (2) Heat treatment, keep warm at 130℃ for 2h±6 min; place the sample flat on A4 copy paper or glass, without contacting the box wall, and heat evenly; (3) After removal, cool at room temperature of 23±2℃ for 30 min and measure the length after shrinkage: L1(MD), W1(TD); Longitudinal (MD) thermal shrinkage rate ; Transverse (TD) heat shrinkage rate ; Take the arithmetic mean of 5 samples, keep 2 decimal places, and take the maximum value as the data and record it.

[0064] II. Peel Strength Test Cut the diaphragm sample into strips 20 mm wide and at least 150 mm long. Apply 20 mm wide 3M tape to the second coating surface of the diaphragm. Roll the strip back and forth three times with a 2 kg rubber roller at 300 mm / min to ensure tight adhesion between the tape and the coating. Let the sample stand at room temperature for 20 minutes. Install the fixed strip onto the clamps of a universal tensile testing machine, adjusting the clamps to make a 180° angle between the sample and the tape. Set the test speed (5-50 mm / min), start the machine, and record the force changes during the peeling process until the tape is completely peeled off. Calculate the peel strength using the following formula: Peel strength (N / m) = Average peel force (N) / Sample width (m); Five parallel samples were tested for each sample, and the arithmetic mean was taken as the final peel strength.

[0065] III. Injection Time Test Using a single-port electrolyte injection machine, set the same injection volume (e.g., 380g) and the same injection process parameters (vacuuming, maintaining a negative pressure of -100kPa to -85kPa on the battery and injection cup for 5 minutes; closing the needle valve, isolating the battery and injection cup, then using vacuum back suction to draw 380g of electrolyte into the injection cup, opening the needle valve, letting it stand for 2 minutes, and then applying a positive pressure of 80-90kPa), and record the time required from the start of positive pressure injection to the complete injection of electrolyte into the cell. Repeat the test 3 times for each cell, and take the arithmetic mean as the final injection time.

[0066] IV. DCR Test The lithium battery was charged at a constant current of 1 / 3C to 3.65V, then charged at a constant voltage to the cutoff current of 0.05C, allowed to rest for 30 minutes, and then discharged at a constant current of 1 / 3C to 2.5V, allowed to rest for 30 minutes. This cycle was repeated three times, and the discharge capacity of the third discharge was taken as C0. The battery was then charged at a constant current of 1 / 3C to 3.65V, then charged at a constant voltage to the cutoff current of 0.05C, allowed to rest for 30 minutes, and then discharged at a constant current of 1 / 3C to 50% SOC, allowed to rest for 120 minutes, and then discharged at a constant current of 2C for 10 seconds. The discharge current corresponding to the 2C rate is I = 2 × C0 (unit: A). The discharge start voltage and discharge end voltage were recorded. The discharge rate (DCR) was calculated using the following formula: DCR (mΩ) = (Discharge initiation voltage - Discharge termination voltage) / Discharge current × 1000; Each battery was tested three times, and the arithmetic mean was taken as the final DCR value.

[0067] V. Cycle Performance Test: Charge the battery at a constant current of 1C to 3.65V, then charge at a constant voltage to the cutoff current of 0.05C, and let it rest for 30 minutes; discharge at a constant current of 1C to 2.5V, and let it rest for 30 minutes. Repeat the above cycle for 500 cycles, record the charge / discharge capacity per cycle, and calculate the cycle capacity retention rate. Cycle capacity retention = (Discharge capacity in week n / Discharge capacity in week one) × 100%; Three parallel samples were tested for each battery, and the arithmetic mean was taken as the final cycle capacity retention rate.

[0068] VI. Thermal runaway test of individual battery cells (1) Pre-charge and discharge treatment: The lithium battery cell is discharged at a constant current of 1 / 3C to the discharge termination voltage (2.5V); rested for 1h; then charged at a constant current of 1 / 3C to the charging termination voltage (3.65V), switched to constant voltage charging until the charging current drops to 0.05C, and rested for 1h after charging; (2) Installation of heating device: Use high temperature tape to fix the heating wire and thermocouple to the lithium battery cell, place them in the ARC calorimeter chamber, adjust the position of the lithium battery cell to ensure that it does not contact the cavity of the calorimeter chamber; (3) Heating procedure: The lithium battery cell is heated from room temperature to the initial experimental temperature (200±3℃). The temperature rise rate of the lithium battery cell (center of the cell) is detected. If the temperature rise rate dT / dt < 0.02℃ / min, the temperature is increased in increments of 5℃. Each temperature increment is held for 30 min or until the temperature rise rate stabilizes. The above steps are repeated until the temperature rise rate dT / dt ≥ 0.02℃ / min. At this point, heating is stopped, the adiabatic environment is maintained, and the temperature change of the cell is recorded until thermal runaway occurs or the temperature drops below the peak value.

[0069] (4) Judgment conditions: a) T1 is the starting temperature of the battery cell's self-heating, determined by dT / dt ≥ 0.02℃ / min; b) T2 is the initial thermal runaway temperature of the battery cell, determined by dT / dt ≥ 1℃ / min; The above judgment is based on the temperature rise rate at the center of the large surface area of ​​the lithium battery.

[0070] VII. Particle Size Testing To determine the particle size of silica generated by in-situ hydrolysis in the first coating, a simulation experiment was conducted using the same reaction conditions as the diaphragm preparation process: the first slurry (alkoxysilane-ethanol solution) was placed in a constant temperature and humidity chamber, with the temperature set at 55-66℃ and the relative humidity at 60%-80%, and kept at this temperature for 2 hours to allow the alkoxysilanes to fully hydrolyze. The white precipitate generated by hydrolysis was collected, washed three times with ethanol, and vacuum dried at 60℃ for 12 hours to obtain silica powder.

[0071] The silica powder was observed using a field emission scanning electron microscope (FE-SEM) with an accelerating voltage of 5-10 kV and a magnification of 50,000-100,000 times. At least 100 particles were randomly selected to measure their Feret diameter, and the arithmetic mean was taken as the silica particle size.

[0072] 8. Coating thickness test and interface transition layer test (1) Testing principle Scanning electron microscopy (SEM) was used to observe the cross-sectional morphology of the membrane. Elemental line scanning or point-by-point analysis of the cross-section was performed using energy dispersive spectroscopy (EDS). By detecting abrupt changes in the content of silicon (Si) and aluminum (Al) along the thickness direction, the boundary positions of the first coating, the interface transition layer, and the second coating were determined, and the thickness of each layer was measured.

[0073] (2) Sample preparation Cut the diaphragm sample into 5mm × 10mm pieces and immerse them in liquid nitrogen for 2-5 minutes. Once the sample is completely brittle, use tweezers to hold both ends of the sample and quickly break it off to obtain a flat, naturally brittle fracture surface. Adhere the brittle fractured sample to the sample stage using conductive double-sided tape, with the brittle fracture surface facing upwards. Perform gold sputtering on the sample using an ion sputtering system. The sputtering conditions are: current 10-20mA, time 60-120s, and gold layer thickness approximately 10-20nm.

[0074] (3) Test conditions Accelerating voltage: 5-20kV (adjustable according to sample conductivity), working distance: 2-30mm, magnification: 500-500000×, scanning mode: secondary electron (SE) and backscattered electron (BSE) modes, silicon drift detector (SDD), acquisition time: 30-120s, spectral range: 0-20keV, quantitative analysis: using ZAF or CL correction method. (4) Determination of benchmark points The interface between the polyolefin base film and the first coating in the diaphragm cross section was taken as the zero displacement point (0 μm). In the base film area, the EDS test results showed that the C element content was the highest (usually >90%), while the contents of elements such as Al and Si were extremely low (all <1%), thus confirming the position of the reference point.

[0075] (5) Boundary location and mutation point determination method EDS tests were performed point by point along the vertical direction of the base film surface, starting from the reference point (0 μm) and moving towards the coating surface. The Si and Al contents at each test point were recorded. The boundaries of each layer were determined based on the abrupt changes in elemental content. ① Determination of the boundary between the first coating and the interface transition layer (first abrupt change point) Moving from the reference point toward the coating direction, when the Al element content first shows a significant increase, this position is determined as the boundary between the first coating and the interface transition layer. Mutation determination criteria: The Al element content increases from <1% to ≥5%, and the change rate of Al content between the two test points before and after this position is ≥100%; then the area before this boundary (closer to the base film side) is the first coating layer, and the area after this boundary (far from the base film side) is the interface transition layer.

[0076] ② Determination of the boundary between the interface transition layer and the second coating (second abrupt change point) Continue moving towards the coating direction. When the Si element content decreases to a low level and the Al element content tends to stabilize, this position is determined as the boundary between the interface transition layer and the second coating. The criteria for determining a mutation are: if the Si content decreases from >20% to ≤5% while the Al content increases to ≥45% and tends to stabilize (the Al content change is ≤5% at two consecutive test points); then the region before this boundary (closer to the base film side) is the interface transition layer, and the region after this boundary (far from the base film side) is the second coating layer.

[0077] (6) Thickness measurement Based on the layer boundaries determined by the above method, the following dimensions are measured in the SEM cross-sectional image along a direction perpendicular to the base film surface: First coating thickness: the distance from the reference point (0 μm) to the first abrupt change point; Interface transition layer thickness: the distance from the first abrupt change point to the second abrupt change point; Second coating thickness: the distance from the second abrupt change point to the air-side surface of the diaphragm; At least 10 different locations were randomly selected for measurement of each sample, and the arithmetic mean was taken as the final thickness of each coating.

[0078] IX. Porosity Testing (1) Sample preparation: Take the diaphragm sample and cut it into small pieces of about 5mm×10mm. Place it in the mold, immerse it in epoxy resin, and keep it under vacuum and pressure at -0.08MPa for 30min to allow the resin to penetrate into the pores. After taking it out, place it in a 60℃ oven to cure for 12h to allow the resin to harden completely. (2) Polishing: The cured sample was successively water-polished with 400 grit, 800 grit, 1500 grit and 3000 grit sandpaper, and finally mirror-polished with diamond polishing liquid to ensure that the cross section of the diaphragm is flat without scratches and without particle shedding; the polished sample was ultrasonically cleaned with deionized water for 5 min and dried in a 60℃ oven for 2 h. (3) Spraying with gold: Spraying the obtained sample with gold (5-10nm); (4) Image acquisition: Scanning electron microscope (SEM) was used for image acquisition. The accelerating voltage was 5-10kV and the magnification was 20,000-50,000 times. Backscattered electron (BSE) mode was used (the area filled with resin in the pores appeared dark / black, and the solid particles appeared light). At least 5 different fields of view were randomly selected in the interface transition layer area and the main area of ​​the second coating for image acquisition. The acquisition area of ​​each field of view was not less than 2μm×2μm to ensure that the image was clear and had good contrast. (5) Porosity calculation: The collected SEM images are processed using image analysis software (such as ImageJ): The images are converted to grayscale; a grayscale threshold is set to divide the image into a porous phase (dark area, corresponding to the resin-filled area) and a solid phase (bright area, corresponding to the particles); (3) The percentage of the number of pixels in the porous phase to the total number of pixels is counted, and the porosity is calculated using the following formula: Porosity (%) = (Number of pore phase pixels / Total number of pixels) × 100% Calculate a porosity value for each field of view, and take the arithmetic mean of at least 5 fields of view as the final porosity of the region, while recording the standard deviation.

[0079] Table 1

[0080] Based on Example 1, Comparative Example 1, and Table 1, it can be seen that the separator prepared using the step-by-step coating method exhibits significantly reduced peel strength, significantly increased thermal shrinkage rate, a significantly lower thermal runaway trigger temperature after battery assembly, and a significantly prolonged electrolyte injection time. This indicates that the dual-layer simultaneous coating process employed in this application can form a continuous transition interface structure between the two coating layers, effectively improving the bonding strength between the coatings and the thermal stability of the separator, while also improving the electrolyte wetting efficiency.

[0081] Based on Example 1, Comparative Example 2, and Table 1, it can be seen that when the positions of the first and second coatings are interchanged, the peel strength of the separator decreases significantly, the thermal shrinkage rate increases significantly, and the thermal runaway trigger temperature of the battery decreases significantly. This indicates that it is necessary to place the small-particle-size silica coating on the side closer to the base film and the large-particle-size ceramic coating on the side farther from the base film. In this order, the small particles can be effectively embedded in the gaps between the large particles, forming a nested particle structure, thereby obtaining good interfacial adhesion and thermal stability.

[0082] Based on Example 1, Comparative Example 3, and Table 1, it can be seen that because water is used as the solvent in the first slurry, tetraethyl orthosilicate is immiscible with water, resulting in a layered emulsion state. Due to the low density of tetraethyl orthosilicate, it floats on the water surface and cannot be properly coated to form a film. This demonstrates that using alcohol-based solvents to prepare the first slurry is crucial for ensuring coating feasibility and coating uniformity.

[0083] Based on Example 1, Comparative Example 4, and Table 1, it can be seen that the membrane formed by directly mixing silica and alumina particles and then coating them in one step, although having a similar thermal shrinkage rate as in Example 1, exhibits significantly reduced peel strength and a markedly prolonged injection time. This indicates that simple particle mixing cannot form an ordered nested particle structure and a dense interfacial transition layer, nor can it effectively retain silanol groups in the coating, thus sacrificing interfacial adhesion and injection efficiency. The ordered bilayer structure of this application has significant advantages over the disordered mixed structure.

[0084] Referring to Examples 1-4 and Table 1, it can be seen that when switching between alkoxysilane compounds (tetraethyl orthosilicate and methyl orthosilicate) and ceramic materials (alumina and zirconium dioxide), the resulting separators all exhibit low thermal shrinkage, high peel strength, and good cycle stability. No thermal runaway phenomena were observed in the batteries during thermal runaway testing. This demonstrates that the technical solution of this application has good raw material adaptability, is not dependent on specific raw material types, and can control the porosity of the interface transition layer and the second coating within a suitable range by adjusting process parameters such as oven temperature, air frequency, and conveyor belt speed, thus contributing to obtaining separators with excellent overall performance.

[0085] Based on Examples 1, 5-6, and Table 1, it can be seen that when the oven temperature is too low, the peel strength of the diaphragm decreases significantly, the thermal shrinkage rate increases, and the cycle stability decreases significantly. When the oven temperature is too high, the injection time is significantly prolonged, and the peel strength also decreases. This is because excessively low temperatures are not conducive to the complete hydrolysis of the organosilicon material and the complete curing of the coating, resulting in a non-dense coating structure. Excessively high temperatures may cause the hydrolysis reaction to be too vigorous, making it difficult for the silanol groups to be retained in the coating. At the same time, the coating may generate internal stress due to excessively rapid drying. Therefore, controlling the drying and curing temperature within a suitable range is crucial for obtaining a diaphragm with excellent overall performance.

[0086] Combining Examples 1, 7-8, and Table 1, it can be seen that when the thickness of the first coating is varied within the range of 0.5-1.5 μm, the key performance characteristics of the separator, such as thermal shrinkage rate, peel strength, and electrolyte injection time, remain at a good level, and no thermal runaway phenomenon is observed in the battery during the thermal runaway test. Specifically, when the thickness of the first coating is relatively thin, the thermal shrinkage rate increases slightly but remains at a low level; when the thickness of the first coating is relatively thick, the DC internal resistance of the battery increases slightly and the cycle retention rate decreases slightly, but all indicators still meet the normal usage requirements of lithium batteries. This indicates that controlling the thickness of the first coating within the above range can balance the thermal stability and electrochemical performance of the separator, exhibiting good process tolerance.

[0087] The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit the scope of protection of this application. Although this application has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application, but such modifications or substitutions are all within the scope of protection of this application.

Claims

1. A diaphragm, characterized in that: Including the base film; A first coating is disposed on at least one surface along the thickness direction of the base film, the first coating comprising silicon dioxide; A second coating is disposed on the surface of the first coating away from the base film, and the second coating comprises a ceramic material; An interface transition layer is located between the first coating and the second coating, and the interface transition layer contains both the silicon dioxide and the ceramic material; The particle size of the silicon dioxide is smaller than that of the ceramic material.

2. The diaphragm as described in claim 1, characterized in that: The silicon dioxide has a particle size of 50-200 nm, and / or the ceramic material has a particle size of 200-500 nm.

3. The diaphragm as described in claim 1, characterized in that: The porosity of the interface transition layer is less than that of the second coating.

4. The diaphragm as described in claim 3, characterized in that: The porosity of the interface transition layer is 10%-20%, and / or the porosity of the second coating is 20%-40%.

5. The diaphragm as described in claim 1, characterized in that: The first coating also includes silanol groups.

6. The diaphragm as described in claim 1, characterized in that: The ceramic material includes at least one of alumina, zirconium dioxide, and titanium dioxide.

7. The diaphragm according to any one of claims 1-6, characterized in that: The thickness of the first coating is 0.5-1.5 μm, and / or the thickness of the second coating is 2-3 μm, and / or the thickness of the interface transition layer is 0.5-1.6 μm.

8. A method for preparing a diaphragm, characterized in that: Includes the following steps: S1, alkoxysilane compounds are mixed with alcohol solvents to obtain the first slurry; The adhesive is mixed with water to obtain a slurry, and the slurry is mixed with ceramic material to obtain a second slurry; S2, the first slurry and the second slurry are simultaneously coated onto the base film to form a wet first slurry layer and a wet slurry layer; wherein, the first slurry layer is located between the base film and the second slurry layer; S3: The base film obtained in S2 after coating is dried and cured to obtain a diaphragm containing a first coating layer, an interface transition layer and a second coating layer.

9. The method for preparing the diaphragm as described in claim 8, characterized in that: S1 satisfies at least one of the following characteristics: (a) The alkoxysilane compounds include at least one of methyl orthosilicate, ethyl orthosilicate, methyl ethyl orthosilicate, propyl orthosilicate, and methyl propyl orthosilicate; (b) The mass ratio of the ceramic material to the binder is (60-120):1; (c) The first slurry has a solid content of 20%-60% and a viscosity of 5-50 mPa·s; (d) The second slurry has a solid content of 30%-40% and a viscosity of 60-140 mPa·s.

10. A lithium battery, characterized in that: It includes a positive electrode, a negative electrode, a separator as described in any one of claims 1-7, or a separator prepared by the method described in any one of claims 8-9.